Analysis of the Satisfaction of Nursing Students towards E-learning of the Medical-Surgical Nursing Subject during Pandemic - Putu inge ruth suantika; Yustina Ni Putu Yusniawati (JKP (Jurnal Keperawatan Padjajaran), 2022)
Background: The whole world is dealing with the covid-19 pandemic. Therefore, the government has taken a policy to transform the education system from in-class to remote learning. Nursing students are adapting to this system, maintaining learning activities through unfamiliar online methods. One of the subjects they take during this pandemic is Medical-Surgical Nursing. This online learning system has created new challenges in the teaching-learning process on the Medical-Surgical Nursing subject. Students tend to feel disinterested, which leads to a sense of dissatisfaction during online learning.